TMET-16. DIRECT DETECTION OF 2HG AND GLUTAMATE PRODUCTION USING HYPERPOLARIZED [1-13C-5-12C]-Α-KETOGLUTARATE IN CELL AND IN VIVO GLIOMA MODELS. (14th November 2022) - Hong, Donghyun; Kim, Yaewon; Mushti, Chandrasekhar; Minami, Noriaki; Gillepspie, Anne Marie; Batsios, Georgios; Taglang, Celine; Cherukuri, Murali; Wu, Jing; Viswanath, Pavithra; Swenson, Rolf; Vigneron, Daniel; et al.
Abstract: Mutant IDH leads to 2HG production, which drives glioma development. 13 C MRS monitoring of hyperpolarized [1- 13 C]α-ketoglutarate (αKG) metabolism to 2HG and glutamate provides a non-invasive assessment of the IDH mutation and normal metabolism, respectively. However, monitoring 2HG production in vivo has been challenging because its resonance is within 0.1 ppm of the natural abundance [5- 13 C]αKG signal of the [1- 13 C]αKG substrate. Here, we utilized [1- 13 C -5-12C]αKG, which eliminated the [5- 13 C]αKG peak. This new approach, combined with an optimized sequence, made it possible to readily monitor the production of both 2HG and glutamate in cells and in vivo in healthy rats or rats with orthotopic patient-derived glioma. Hyperpolarized [1- 13 C -5- 12 C]αKG was injected into genetically engineered NHAIDHmut cell lysates, healthy rats, and rats implanted orthotopically with BT257 cells intravenously. 1-D dynamic 13 C MRS spectra from cells and in vivo slab spectroscopy data were then acquired using an 11.7 T NMR system and a 3 T pre-clinical scanner, respectively. Injection of the hyperpolarized [1- 13 C -5- 12 C]αKG into cell lysates showed clearly detectable dynamic conversion of hyperpolarized [1- 13 C-5- 12 C]αKG to 2HG and glutamate. The normal brain showed clear production of glutamate but no 2HG was detected. In tumor-bearing rats, we were able to clearly detect the dynamic production of both 2HG and glutamate. This study demonstrated the utility of hyperpolarized [1- 13 C-5- 12 C]αKG as a substrate to clearly assess 2HG production without the confounding presence of the natural abundance peak which cannot be distinguished from 2HG in vivo . Importantly, the detection of 2HG provides a clear indicator of the IDH mutation within the tumor.